Resolvin D1 improves allograft osteointegration and directly enhances osteoblasts differentiation - Pinto, Noy; Klein, Yehuda; David, Eilon; Polak, David; Steinberg, Daniel; Mizrahi, Gilad; Khoury, Yasmin; Barenholz, Yechezkel; Chaushu, Stella (Frontiers in Immunology, 2023)
Introduction: Allografts are the most common bone grafts for repairing osseous defects. However, their use is associated with an increased risk for infections, donor disease transmission and osteointegration deficiency. Resolvin D1 (RvD1) is an endogenous lipid with a scientifically proven pivotal role in inflammation resolution and osteoclastogenesis inhibition. Yet, its biological relevance as a potential bone regenerative drug has been scarcely studied. Here, we aim to investigate the RvD1 effect on allograft osteointegration in the alveolar bone regeneration (ABR) murine model. Methods: ABR model consisted of osseous defects that were generated by the extraction of the maxillary first molar in C57BL/6 mice. The sockets were filled with allograft and analyzed via RNA sequencing. Then they were locally injected with either RvD1 or saline via single or repeated administrations. The mice were sacrificed 2W after the procedure, and regenerated sites were analyzed using 𝜇CT and histology. In Vitro: First, MC3T3-E1 preosteoblasts were plated with IL-17 pro-inflammatory medium, and RANKL/OPG ratio was measured. Secondly, the MC3T3-E1 were cultured w/o RvD1, for 3W. Osteoblasts' markers were evaluated in different days, using qRT-PCR and Alizarin Red staining for calcified matrix. Results: In vivo, neither allograft alone nor single RvD1 administration promote bone regeneration in comparison to the control of spontaneous healing and even triggered an elevation in NR1D1 and IL1RL1 expression, markers associated with inflammation and inhibition of bone cell differentiation. However, repeated RvD1 treatment increased bone content by 135.92%±45.98% compared to its specific control, repeated sham, and by 39.12%±26.3% when compared to the spontaneous healing control group (n=7/group). Histologically, repeated RvD1 reduced the number of TRAP-positive cells, and enhanced allograft osteointegration with new bone formation. In vitro, RvD1 rescued OPG expression and decreased RANKL/OPG ratio in IL-17 pro-inflammatory conditions. Furthermore, RvD1 increased the expression of RUNX2, OSX, BSP and OC/BGLAP2 and the mineralized extracellular matrix during MC3T3-E1 osteoblasts differentiation. Conclusions: Repeated administrations of RvD1 promote bone regeneration via a dual mechanism: directly, via enhancement of osteoblasts’ differentiation and indirectly, through reduction of osteoclastogenesis and RANKL/OPG ratio. This suggests that RvD1 may be a potential therapeutic bioagent for osseous regeneration following allograft implantation.